Islamic Personality Model as Psychometric Tool To Assess Creditworthiness of Micro Financing - Hardiansyah Hardiansyah; Euis Amalia; Abdul Hamid (ETIKONOMI, 2023)
This study aims to develop an Islamic personality model as a psychometric tool to assess creditworthiness as an alternative predictive character analysis for micro businesses. The method designed to formulate the proposed model coded in R Studio uses two approaches. First, we modify Moslem Religiosity Personality Inventory and then frame a structural model based on Partial Least Square. Subsequently, we use the random forest technique to see the model's accuracy. The result shows a valid and reliable model and performs with 89.47 % accuracy with an Area Under Curve -Receiver Operating Characteristic of 90.06 %. This model implies a solution to strengthen the assessment of the character of creditworthiness of a potential micro-business and helps Islamic Financial Institutions to assess prospective micro-business to determine credit risk and pricing.JEL Classification: B41, D81, D87, G21, P43How to Cite:Hardiansyah., Amalia, E., & Hamid, A. (2023). Islamic Personality Model as Pychometric Tool To Access Creditworthiness of Micro Financing. Etikonomi, 22(1), 233–246. https://doi.org/10.15408/etk.v22i2.30370.